Hubungan Kecemasan, Peran Suami, Dan Peran Bidan Terhadap Kejadian Ketuban Pecah Dini Di Rumah Sakit Tugu Ibu Cimanggis Kota Depok : The Relationship between Anxiety, the Role of Husbands, and the Role of Midwives in the Premature Rupture of Membranes at Tugu Ibu Cimanggis Hospital, Depok City - Suharyati (Dohara POAJ, 2024)
Introduction: Premature rupture of membranes is the rupture of the membranes before labor begins at any stage of pregnancy. Anxiety, the role of the husband, and the role of the midwife are factors that can influence the incidence of premature rupture of membranes. This study aims to determine the relationship between anxiety, the husband's role, and the midwife's role in the incidence of premature rupture of membranes at Tugu Ibu Cimanggis Hospital, Depok City in 2022. Methods: Using descriptive analytics with a cross-sectional approach. The sampling technique used was total sampling with a total of 21 postpartum mothers. Results: The results showed that there was a relationship between anxiety and the incidence of premature rupture of membranes with a p-value of 0.000, the role of the husband in the incidence of premature rupture of membranes with a p-value of 0.008, and the role of midwives with premature rupture of membranes obtained a p-value of 0.021. Discussion: This study is a relationship between anxiety the husband's support and the role of the midwife on the incidence of premature rupture of membranes at Tugu Ibu Cimanggis Hospital, Depok City. Advice for mothers giving birth is to be able to increase their knowledge and understanding of tips for having a healthy pregnancy and preparing for safe and comfortable deliveries so that they are free from complications and emergencies in labor.